AB0489 Pulse Cyclophosphamide Therapy of Lupus-Nephritis and Its Course through the Maintenance Therapy. (10th June 2014) - Lukac, J.; Lukacova, O.; Canicova, A.; Tuchynova, A.; Rovensky, J.; Zanova, E.
Abstract : Background: Lupus-nephritis (LN) is a serious organ involvement and important factor of morbidity and mortality in patients (pts) with systemic lupus erythematosus. As initial treatment of LN, high doses of glucocorticoids (GK), pulses of cyclophosphamide (PT CY) or mycophenolate mofetil (MMF) is recommended. Initial treatment is followed by subsequent (maintenance) therapy. There are few information about course and relapses of LN through the maintenance therapy. Methods: In retrospective study, 36 pts with SLE and LN were hospitalized in National Institute of Rheumatic Diseases Piestany from 1996 – 2013 years. Effectiveness of initial treatment of PT CY on LN activity, course of LN and occurrence of relapses through maintenance therapy was evaluated. Results: Total 36 patients (pts) with SLE and LN were treated with PT CY 0, 5-1 g/m 2 monthly for 6 month. There were 31 female and 5 male pts with with a mean age 38.7 yrs on the onset of SLE, with disease duration 9.62 yrs (2 to 25 yrs). Anti-dsDNA antibodies were positive in 25 pts at the onset of the therapy and in 12 pts persisted after PT CY. Hypocomplementemia before therapy was recorded in 34 of 36 pts. Renal failure with creatinine elevation at the beginning of the PT CY was in 6 of 36 pts. Overall SLE activity was evaluated by SELENA SLEDAI. After initial treatment of PT CY, complete renal response was reached in 34 pts, partial in 2 pts. Low complement was normalized in 64.7%. After that, four types of maintenance therapy was introduced: 12 pts PT CY 0, 5-1 g/m 2 each three months, 8 pts azathioprine from 50 to 100 mg a day, 6 pts MMF 2 g per day, 10 pts cyclosporine A 100 to 150 mg a day. Combination with belimumab had 1 pts and with hydroxychloroquine 10 pts. The dosage of GK through the maintenance therapy was from 10 – 25 mg of prednisone. In 16 pts suppression persist through the following up, in 20 pts relapse of LN appeared. Time to relapse after PT CY was 43 months in average (5 - 116 months). At AZA therapy, there were 11 relapses, 3 at MMF, 2 at cyclosporine A, 4 at GK maintenance therapy. In group of pts with LN relaps, 13 pts had anti-dsDNA autoantibodies. In another 5 pts were anti-dsDNA antibodies negative in time of LN reactivation. After LN relapse, PT CY was repeatedly introduced – again with complete or partial renal response. Conclusions: Pulse CY therapy is effective almost in all pts with SLE and LN. Relapses in the phase of maintenance therapy occurred in more than 50% of pts. Relapses of LN can appear even in pts without anti-dsDNA antibodies. Tight control of SLE activity is necessary in all pts. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3905